ประสบการณ์การจัดการสาธารณภัยของพยาบาลวิชาชีพในเหตุการณ์สินามิ - ปรารถนา ยามานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The purpose of this qualitative study was to explore the disaster management meaning and the experiences of professional nurses during Tsunami. The Husserl phenomenological approach was employed in this study. Study participants were selected by using purposive sampling from a general hospital in Pangya. Nineteen professional nurses were willing to participate in this study. In-depth interview with tape-record was used to collect data. All interviews were transcribed verbatim and analyzed by using content analysis of Colaizzi. The study findings showed substantial theme of the disaster management meaning consisting of 2 categories: 1) performing with routine disaster management plan; and 2) solving an emergent problem. According to content analysis, the experiences of professional nurses during Tsunami were emerged into 3 categories as follows: Category 1: Managing disaster including: 1.1 Overload of victim screening 1.2 Lack of coordination in referral 1.3 Messy documentation 1.4 Tiring staff need more help 1.5 Insufficient medical equipments, must ask from other hospitals 1.6 Being conflict 1.7 Using all materials in hand, no time for cleaning 1.8 Failure of communication, requesting translators Category 2: Managing emotion including: 2.1 Responsibility comes first 2.2 Fearful whereas cannot leave patients 2.3 Controlling the mind, pity, working until exhausted Category 3: Managing disaster results including: 3.1 Concerning others rather than oneself 3.2 Impressing in teamwork